Japanese Perception of Arabic and English Corporate Logos - Eibo, Ahmad; Yamashita, Toshiyuki; Kasamatsu, Keiko (Arab Journal for Sciences and Research Publishing, 2016)
Recently, Japanese are increasingly interacting with Arabic logotypes as a consequence of growing trade between Japan and Arab countries. This paper aims to examine Japanese consumer perception of Arabic alphabetic logos compared to English of the same corporate. With 20 logos as stimulus of 10 globally well-known companies (FedEx, Burger King, CNN, Subway, Tide, Baskin-Robbins, Vodaphone, Starbucks, Coca Cola, and Adidas), a questionnaire survey was curry out by fifty undergraduate students (35 males, 15 females) corresponding to our explanatory study design. In (SPSS) data entry, Factor Analyses of interval sampling extracted three main images for corporate logos, that is “Traditional and Consistent,” “Familiar and Favorable,” and “Creative and Innovative” and revealed that Arabic logos are creative but unfamiliar to Japanese in result. Moreover, another result was detected by Rough Sets analyses of (ROSE2) showing that Japanese are more familiar with English alphabetic logos than they are with Arabic alphabetic logos. Our conclusion suggests that to enhance the recognition of Arabic corporate logos in Japan, it is essential to familiarize Japanese with the Arabic alphabet.